Sedentary behavior is associated with disability and multimorbidity in older adults during the COVID-19 pandemic: a cross-sectional survey (Research, Society and Development, 2022)
Objective: We described sedentary behavior during the COVID-19 pandemic in Brazilian older adults and explored      whether highly sedentary behavior was associated with multimorbidity, physical activity levels, adoption of physical distancing, perceived social isolation, disability, and depressive symptoms. Methods: We surveyed 184 older adults and gathered information on sedentary behavior, multimorbidity, physical activity, adoption of social distancing, perceived social isolation, disability, and depressive symptoms. Then, we investigated the association between highly sedentary behavior and these factors. Results: 26% of participants reported high levels of sedentary behavior, spending 5 hours per day in sitting (median). Highly sedentary behavior during COVID-19 pandemic was associated with multimorbidity (OR: 2.78, 95% CI 1.12-6.89) and disability (OR: 1.08, 95% CI 1.02-1.16). Conclusion: The prevalence of highly sedentary behavior in older adults during the pandemic was 26%. High sedentary behavior was associated with disability and multimorbidity in them. These findings can be used to guide the academia, the public sector, and health professionals to develop integrated initiatives to monitor and to decrease sedentary behavior especially in older adults with disability and multimorbidity during and beyond the COVID-19 pandemic.